1995
DOI: 10.1182/blood.v86.7.2590.2590
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cells induce myeloid and lymphoid development of the sorted hematopoietic stem cells in vitro

Abstract: Regulation of development of hematopoietic stem cells was examined by culturing Lin- c-Kit+ Sca1+ stem cells sorted from bone marrow (BM) cells by fluorescence-activated cell sorting on a layer of TBR59, a BM stromal cell line established from simian virus 40 T-antigen gene transgenic mice. The sorted stem cells did not show self-renewal, but two waves (at 7 and 13 days) of a cobblestone formation were induced by the stromal cell layer. The cobblestones were formed by finite cell division (eight divisions on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Yolk sac cells were inoculated into 0.8% methylcellulose and cultured in the presence of erythropoietin (2 U/ml) and stem cell factor (SCF; 50 ng/ml) (Okuyama et al ., 1995), and the numbers of colonies (colony‐forming unit‐erythroid, CFU‐E) formed were counted.…”
Section: Methodsmentioning
confidence: 99%
“…Yolk sac cells were inoculated into 0.8% methylcellulose and cultured in the presence of erythropoietin (2 U/ml) and stem cell factor (SCF; 50 ng/ml) (Okuyama et al ., 1995), and the numbers of colonies (colony‐forming unit‐erythroid, CFU‐E) formed were counted.…”
Section: Methodsmentioning
confidence: 99%
“…Its immortalizing activity is based upon its interaction with the retinoblastoma protein and p53, and their regulators p21 CIP1/WAF1 and p16 INK4 , and the recently described tumor suppressor gene SEN6 leading to extended proliferation (Smith and Pereira-Smith, 1996). Rather than using the commercially available 'Immorto' mouse (Jat et al, 1991) or the transient transgenic approach (Okuyama et al, 1995a;Okuyama et al, 1995b), we generated two new mouse lines, Tag5 and Tag11, that express the tsA58 gene under the control of the β-actin or PGK gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to further clarify the MHC preference between HSCs and stromal cells and investigate the mechanisms underlying the preference, we analyzed the cobblestone colony formation of HSCs under the monolayers of the MHC‐matched and ‐mismatched stromal cells derived from fetal bones. Since the cobblestone colony is composed solely of cells which are phenotypically identical to HSCs [52, 53], and since the cobblestone area‐forming cells differentiate not only into myeloid and erythroid but also lymphoid cells [54, 55], the cobblestone assay permits the direct measurement of differentiating HSCs in the context of the interaction with stromal cells. In the present study, we have shown that two to five times more HSCs are required for obtaining 50% cobblestone colony formation when BMCs were added to the MHC‐mismatched stromal cell layers (Table 2).…”
Section: Discussionmentioning
confidence: 99%